Low temperature ITO thin film deposition for solar cells - Seraffon, Maud (Cranfield University, 2008)
The electrical and optical properties as well as the microstructure of indium tin oxide thin films deposited on glass and flexible substrates is demonstrated in this project report. This project is a part of an MSc in Advanced Materials at Cranfield University. The understanding and improvement of indium tin oxide coatings deposited by magnetron sputtering on both glass and polymer substrates has been an area of extensive research in the last decade. This technology appears to be very interesting in terms of money saving and efficiency in the solar cell domains where the coatings are used in thin film solar cells. Research into the thin film solar cells mechanism, the sputtering process and ITO coatings is reported, along with detailed consideration of the best results obtained in the past in terms of ITO films’ electrical and optical properties. ITO thin films were deposited on glass and different sputtering parameters were changed in order to investigate their influence on the coatings properties: film thickness, chamber pressure, rotation, oxygen amount and sputtering power. A decision was made to establish the best sputtering parameters. These parameters were set to deposit ITO on polyethylene terephthalate (flexible substrate). The samples were also annealed at 150°C and 370°C. An ITO thin film with a resistivity of 1x10-4 Ωcm and a 90% transmissivity was obtained. An Energy Dispersive Spectrometry analysis was finally made on samples showing a substoichiometric composition of the ITO films.
Keywords: Magnetron Sputtering; Indium Tin Oxide; Thin Film; Solar Cells; Flexible Substrates; Annealing; Substoichiometry